Formation of Non-Maxwellian Distribution and Its Role in Collisionless Driven Reconnection (Communications in Computational Physics, 2008)
The dynamical evolution of collisionless driven reconnection is investigatedby using an electromagnetic particle simulation code in a microscopic open system.Strong in-plane electrostatic field is excited in the central region of current sheet under the influence of an external driving field. As a result of the amplification of unmagnetized meandering motion by the electrostatic field particle distribution functionis modified from the shifted Maxwellian to an anisotropic one in the current sheet.An ion hole appears at the center of current sheet in the phase space, where distribution becomes two-peaked and no ions exist in low velocity region between two peaks.The strong modification of distribution function leads to the generation of off-diagonalcomponents of pressure tensor term, which is one of major causes to violate frozen-inconstraint and trigger collisionless reconnection.